A review of transport protocols as candidates for use in a tactical environment - Carter, Michael; Defence Science and Technology Organisation (Australia); Defence Science and Technology Organisation (Australia). Information Networks Division (Edinburgh, S. Aust. : DSTO, 2005)
Transport protocols are an essential part of any modern data network, including military tactical networks. Most networks today, including the Internet, operate mainly using the transport protocol TCP. However, this protocol makes a number of assumptions that make it unsuitable for use in a military environment, which is typically characterised by data links that are impoverished in some way. This paper examines TCP, its deficiencies and many other transport protocols that are evaluated for suitability to a military tactical environment. Many of the essential services of TCP as well as other desirable services can be well met by some of these other protocols in existence today in a way that is more suitable for a military tactical environment.
"AR-013-549"--T.p. verso.
"December 2005"--T.p. verso.
"Information Networks Division, DSTO Defence Science and Technology Organisation"--T.p. verso.
Title from title screen (viewed on Aug.1, 2006).
Includes bibliographical references (p. 28-32).
Text.
Keywords: Communications, Military; Computer network protocols